FATWA METHODOLOGY OF NATIONAL SHARIA BOARD OF INDONESIAN ULAMA COUNCIL IN ISLAMIC ECONOMICS - Iiz Izmuddin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2018)
Abstract: This study aims to find out the methodology of DSN-MUI fatwa in response to the problems of Muslims in Indonesia related to economy. The DSN-MUI comes by issuing its fatwa with a distinctive fatwa methodology, called mutawassitah (moderation) between the mutasâhil (liberal) method and the mutasyaddid (textualist) method. There are about 116 fatwas issued by DSN-MUI from 2000 to present time (2017). The first fatwa on Giro 01/DSN-MUI/IV/2000 and the latest fatwa No. 116/DSN-MUI/II/2017 on Uang Elektronik Syariah. The approach in this study is the mashlahah approach, the jurisprudence (fiqh) principles and madhhab comparison especially mutasyaddid (texstualist) and mutasâhil sects (liberal). This study concludes that the methodology of the DSN-MUI fatwa declaring with moderation methodology is in fact closer to the mazhab of mutasâhil even though the approach of fiqhiyah approaches more closely to the textualist but the subtance is closer to the madhhab mutasâhil.Abstrak: Moderasi Metodologi Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia dalam Perkembangan Ekonomi Syariah. Studi ini bertujuan untuk mengetahui model metodologi fatwa DSN-MUI dalam menjawab persoalan umat Islam di Indonesia yang berkaitan dengan ekonomi. DSN-MUI hadir dengan mengeluarkan fatwanya dengan metodologi fatwa yang khas, yaitu dengan jalan mutawassitah (moderasi) antara metode mutasâhil (liberal) dan metode mutasyaddid (tekstualis). Ada sekitar 116 fatwa yang dikeluarkan oleh DSN-MUI dari tahun 2000 sampai sekarang (2017). Fatwa pertama tentang Giro bernomor 01/DSN-MUI/IV/2000 dan fatwa terakhir bernomor 116/DSN-MUI/II/2017 tentang Uang Elektronik Syariah. Pendekatan dalam studi ini adalah pendekatan mashlahah, kaidah-kaidah fikih dan perbandingan mazhab terutama mazhab mutasyaddid (tekstualis) dan mazhab mutasâhil (liberal). Studi ini menyimpulkan bahwa metodologi fatwa DSN-MUI yang mendeklarasikan dengan metodologi moderasi, kenyataannya lebih mendekati kepada mazhab mutasâhil walaupun proses pendekatan fiqhiyah lebih mendekati mazhab tekstualis, akan tetapi subtansinya lebih mendekati mazhab mutasâhil.Keywords: moderation, fatwa, DSN-MUI, Islamic economic